At the bench: Engineering the next generation of cancer vaccines. Issue 4 (20th August 2019) - Shae, Daniel; Baljon, Jessalyn J.; Wehbe, Mohamed; Becker, Kyle W.; Sheehy, Taylor L.; Wilson, John Tanner
Abstract: Cancer vaccines hold promise as an immunotherapeutic modality based on their potential to generate tumor antigen‐specific T cell responses and long‐lived antitumor responses capable of combating metastatic disease and recurrence. However, cancer vaccines have historically failed to deliver significant therapeutic benefit in the clinic, which we maintain is due in part to drug delivery challenges that have limited vaccine immunogenicity and efficacy. In this review, we examine some of the known and putative failure mechanisms of common first‐generation clinical cancer vaccines, and describe how the rational design of materials engineered for vaccine delivery and immunomodulation can address these shortcomings. First, we outline vaccine design principles for augmenting cellular immunity to tumor antigens and describe how well‐engineered materials can improve vaccine efficacy, highlighting recent innovations in vaccine delivery technology that are primed for integration into neoantigen vaccine development pipelines. We also discuss the importance of sequencing, timing, and kinetics in mounting effective immune responses to cancer vaccines, and highlight examples of materials that potentiate antitumor immunity through spatiotemporal control of immunomodulation. Furthermore, we describe several engineering strategies for improving outcomes of in situ cancer vaccines, which leverage local, intratumoral delivery to stimulate systemic immunity. Finally, we highlight recent innovations leveraging nanotechnology for increasing the immunogenicity of the tumor microenvironment (TME), which is critical to enhancing tumor infiltration and function of T cells elicited in response to cancer vaccines. These immunoengineering strategies and tools complement ongoing advances in cancer vaccines as they reemerge as an important component of the immunotherapeutic armamentarium. Graphical Abstract: Describes how rationally engineered materials are opening up new opportunities for enhancing the immunogenicity and therapeutic efficacy of cancer vaccines.